The level of satisfaction towards happiness index in quantity surveying consultant firm / Exquan Amir Mohamad Daud - Mohamad Daud, Exquan Amir (2021)
The happiness index in the workplace plays an essential role in enhancing employee productivity and output while taking care of their needs. The quantity surveyor has identified as one of the most stressful profession. Four elements have been identified as elements of happiness index, which are Satisfaction, Alignment, Engagement and Well-being. The employee's happiness needs to be considered as it will ensure the organisation productivity and turnover rate. This study aims to determine the elements of happiness index and level of satisfaction of Quantity Surveyors towards Happiness Index. Three objectives have been outlined to achieve the aim of this study which are, to identify the elements of happiness index in workplace, to investigate the level of satisfaction towards happiness index in quantity surveyor consultant firms, and to recommend the strategies in implementing the happiness index in quantity surveyor consultant firms. The research methods are by using questionnaire survey for primary data, literature review for secondary data and the data was analysed by SPSS software. The respondents are quantity surveyors working in quantity surveying consultant firms. The result throughout this finding shows highest score for level of satisfaction of elements of happiness index is engagement, where it consists of sub element emotional engagement and behavioural engagement. Whereas the highest score for strategies to be recommended is rewards as motivation, and it is also one of the most suggested by the respondents. In conclusion, each person has different factors that contribute to their happiness in the workplace.